Field notes contributed by Dick Bierman, spring 1983 - Bierman, Dicket al (1983)
Spring report of birds found in northwest Iowa contributed by Dick Bierman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed